EXAMINING THE WOMAN’S AWAKENING FROM A BAKHTINIAN PERSPECTIVE IN JALIL MAMMADGULUZADEH’S “THE TALE OF THE VILLAGE OF DANABASH” - Akbay, Yakut (Uluslararasi Dil, Edebiyat ve Kultur Arastirmalari Dergisi, 2026)
This study aims to analyse the themes of women’s awakening, social realism, patriarchal structures and ignorance in Azerbaijan in Jalil Mammadguluzadeh’s story “The Tale of the Village of Danabash” from the collection Stories from the Village of Danabash (1894). The text is analysed based on Mikhail Bakhtin’s concepts of heteroglossia, polyphony, dialogue and the carnivalesque. It is argued that the main female character, Zeynep, demonstrates how women, despite being denied basic rights and freedoms in the 19th century, struggled to attain them. A Bakhtinian perspective is important in illuminating Zeynep’s interactions with other characters. The humorous treatment of these interactions makes it possible to question the traditional patriarchal order and open up alternative perspectives. The carnivalesque approach helps the author to address serious issues in a more accessible and critical way and to highlight the absurdity of some social norms. In this context, Zeynep’s experiences should be seen as an active part of social dialogue rather than a passive representation of femininity. A Bakhtinian perspective allows us to see Zeynep’s story as a symbol of social change beyond individual struggle. The significance of this study therefore lies in the examination of Jalil Mammadguluzadeh’s “The Tale of the Village of Danabash” from the perspective of Mikhail Bakhtin’s theoretical concepts, to contextualise the struggle for women’s awakening in 19th-century Azerbaijan.